2010
DOI: 10.1194/jlr.m002618
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of serum angiopoietin-like proteins 3 and 4 in a Finnish population sample

Abstract: Dysregulation of lipid metabolism is closely related with a number of pathological states including atherosclerosis, obesity, and insulin resistance. An extensive amount of data relates elevation of cholesterol and triglycerides (TG) in apolipoprotein (apo)B-containing particles such as VLDL and LDL to increased risk for atherosclerosis. Epidemiological and clinical studies have provided strong evidence that a low level of cholesterol in HDL is also a major risk factor for the development of atherosclerosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
97
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 33 publications
(28 reference statements)
18
97
1
Order By: Relevance
“…Circulating ANGPTL4 levels were negatively associated with HDL‐c and positively associated with triglyceride in Americans 12. On the other hand, no correlation was seen between circulating ANGPTL4 levels with any of these aforementioned parameters in Finnish subjects 37. In the study, we did not observe any significant association between circulating ANGPTL4 levels and HDL‐c, LDL‐c, or triglyceride in nondiabetic participants.…”
Section: Discussioncontrasting
confidence: 69%
“…Circulating ANGPTL4 levels were negatively associated with HDL‐c and positively associated with triglyceride in Americans 12. On the other hand, no correlation was seen between circulating ANGPTL4 levels with any of these aforementioned parameters in Finnish subjects 37. In the study, we did not observe any significant association between circulating ANGPTL4 levels and HDL‐c, LDL‐c, or triglyceride in nondiabetic participants.…”
Section: Discussioncontrasting
confidence: 69%
“…Inhibited LPL was found in a complex with ANGPTL4, and superstoichiometric ratios of ANGPTL4/LPL were required for complete inhibition. These findings may have considerable in vivo significance in light of recent data showing that, in humans, serum ANGPTL4 levels do not correlate with plasma triglyceride levels and that LPL travels bidirectionally across endothelial cells (24,25). These data have led to the suggestion that ANGPTL4 could inhibit LPL in the subendothelial space rather than on the endothelial surface (25).…”
Section: Lplmentioning
confidence: 84%
“…ANGPTL4 could thus inhibit LPL in either the subendothelial space or on the surface of the capillary endothelium, and a number of recent studies support the former option. First, although ANGPTL4 is known to regulate LPL activity in vivo and in vitro, two studies in human populations found no correlation between serum ANGPTL4 and triglyceride levels (24,43). Full-length ANGPTL4 is known to interact with the extracellular matrix in the subendothelial space via its C-terminal domain (44).…”
Section: Discussionmentioning
confidence: 99%
“…S3D), suggesting that the substitution has modest effects on ANGPTL8 function. In contrast to ANGPTL8, adenovirus-mediated expression of ANGPTL3 at levels comparable to those present in human plasma (∼300 ng/mL) (27) did not elicit an increase in plasma TAG or NEFA (Fig. 3A).…”
Section: Angptl8 Expression In Livers Of Mice Causes Hypertriglyceridmentioning
confidence: 99%